2013
DOI: 10.4161/viru.21657
|View full text |Cite
|
Sign up to set email alerts
|

Impact of formulary restriction with prior authorization by an antimicrobial stewardship program

Abstract: In an era of increasing antimicrobial resistance and few antimicrobials in the developmental pipeline, many institutions have developed antimicrobial stewardship programs (ASPs) to help implement evidence-based (EB) strategies for ensuring appropriate utilization of these agents. EB strategies for accomplishing this include formulary restriction with prior authorization. Potential limitations to this particular strategy include delays in therapy, prescriber pushback, and unintended increases in use of un-restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
1
26
0
3
Order By: Relevance
“…This strategy as well has been documented as an effective method in reducing the inappropriate use of select antimicrobial agents. 13 In addition, the Society for Healthcare Epidemiology of America/Infectious Diseases Society of America guidelines refer to the importance of the role that IT and clinical decision support tools play in improving antimicrobial agent use decision making. Indeed, many interviewees commented on the usefulness of incorporating IT, such as real-time alerts, into their computer systems for the conduction of their stewardship activities.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy as well has been documented as an effective method in reducing the inappropriate use of select antimicrobial agents. 13 In addition, the Society for Healthcare Epidemiology of America/Infectious Diseases Society of America guidelines refer to the importance of the role that IT and clinical decision support tools play in improving antimicrobial agent use decision making. Indeed, many interviewees commented on the usefulness of incorporating IT, such as real-time alerts, into their computer systems for the conduction of their stewardship activities.…”
Section: Discussionmentioning
confidence: 99%
“…Although measurement of non-targeted or total antimicrobials is more labor intensive than measuring targeted agents alone, this information is essential to allow for the detection of compensatory increases in the use of other agents, which can lead to the "squeezing the balloon" phenomenon [79]. However, some studies only reported consumption of targeted antimicrobials [8,20,30,44,54,75].…”
Section: Metrics Process Measuresmentioning
confidence: 98%
“…This has the potential to enhance internal audit and reporting capabilities, benchmarking, and assist with antimicrobial stewardship efforts. One academic medical center utilized their CPOE system to enforce prior authorization by the ASP between the hours of 8 a.m.-10 p.m. before allowing orders for doripenem to be placed [26]. This resulted in a significant decrease in doripenem use.…”
Section: Computerized Physician Order-entrymentioning
confidence: 98%